1129 Sex Dependent Effects on Sleep Architecture After Traumatic Brain Injury: Impact on Outcome. (27th May 2020) - Griesbach, G S; Robinson, S E; Howell, S
Abstract: Introduction: Traumatic Brain Injury (TBI) is frequently associated with problems with sleep and diurnal somnolence. After determining if subjective somnolence was associated with sleep disturbances, we investigated if alterations in sleep architecture were associated with cognitive, social and emotional health in a sex dependent manner. For patients receiving positive airway pressure (PAP) treatment, we determined if lack of compliance contributed to cognitive and quality of life issues. Methods: Adult TBI subjects (n=57) were assessed via overnight polysomnography. Mean age was 41 years and mean TBI chronicity was 2.5 years. Overall level of disability was determined by the Mayo Portland Inventory II. Sleep measures included slow wave sleep (SWS), REM latency, percent time in all sleep stages, apnea/hypopnea index, wake after sleep onset (WASO), and arousal index. Outcome measures were the California Verbal Learning Test (CVLT), Montreal Cognitive Assessment (MoCA), Trails A and B, Beck Depression Inventory, and Neuro-QoL. Results: No sex effects for reporting somnolence were found. Besides being associated with increased subjective anxiety and stigma, somnolence was associated with increased arousals, decreases in SWS and higher incidence of REM AHI. WASO and number of arousals had a negative impact on the amount of SWS and sleep efficiency. Men spent significantly more time in REM sleep, which was correlated with higher scores on the MoCA and CVLT. Women showed more disability. Longer latencies to SWS were associated with increased CVLT performance. AHI was associated with increases in emotional/behavioral dyscontrol, fatigue and self-reported sleep disturbance. All effects were statistically significant. Conclusion: Female TBI patients show significant impairments in REM sleep, which may impact learning and memory. Sleep disturbances were associated with poorer cognitive performance and may ultimately affect outcome, as indicated by lower scores on quality of life measures. Support: Centre for Neuro Skills